Application of Self-Cleaning, Fluidised-Bed Slurry Heat Exchangers: Processing of Laterite Ore Slurries for the Extraction of Nickel and Cobalt in High-Pressure-Acid-Leach (HPAL) Plants - B Crossley (The Australasian Institute of Mining and Metallurgy, 2004)
Self-cleaning fluidised bed heat exchangers have demonstrated unparalleled performance internationally for the implementation of indirect heat transfer in severely fouling fluid environments. Recent advances in equipment design have increased the scope of application to include indirect heat transfer in slurry environments, including fouling, scaling and viscous slurries. The ingenious configuration of recirculated cleaning particles through the tubes of vertical shell and tube heat exchangers provides the ability to solve heat transfer problems that arise as a consequence of tube-side fouling during indirect heat transfer to process fluids or slurries. In most cases, the cleaning particles consist of chopped metal wire, however other process-specific materials may be used.